2018
DOI: 10.1007/s40037-018-0449-2
|View full text |Cite
|
Sign up to set email alerts
|

Fostering medical students’ lifelong learning skills with a dashboard, coaching and learning planning

Abstract: IntroductionTo develop lifelong learning skills, students need feedback, access to performance data, and coaching. A new medical curriculum incorporated infrastructural supports based on self-regulated learning theory and the Master Adaptive Learner framework to engage students in reflection and learning planning. This study examines students’ experience with a performance dashboard, longitudinal coaching, and structured time for goal-setting.MethodsFocus groups with first-year medical students explored perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 28 publications
1
27
0
Order By: Relevance
“…Coaching is a well-accepted method of developing leaders in the business community and is increasingly used in developing educators [1,2]. In recent years, coaching learners has become more common in medical education curricula [3][4][5][6][7][8][9]. One-on-one coaching is proven to support medical learners' success academically and to facilitate individual self-knowledge, goal-setting, work-life balance, and reflection [3,9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Coaching is a well-accepted method of developing leaders in the business community and is increasingly used in developing educators [1,2]. In recent years, coaching learners has become more common in medical education curricula [3][4][5][6][7][8][9]. One-on-one coaching is proven to support medical learners' success academically and to facilitate individual self-knowledge, goal-setting, work-life balance, and reflection [3,9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Strengths of this study include the very recent detailed data collected on an entire cohort of medical students, including their career choices. While other studies have reported on managing clinical placements [10][11][12], these prior studies have focused on theoretical aspects [10], staff perspectives [11] or international experiences [13] without reporting detailed educational outcomes, as we have done here.…”
Section: Discussionmentioning
confidence: 99%
“…Oregon Health & Science University (OHSU) transformed to a new time-varying competency-based curriculum, called 'YourMD' in 2014. The redesign included more flexibility for elective time, enrichment opportunities that allowed students to explore different disciplines in medicine, and tailored coaching toward fostering the development of master adaptive learners [13][14][15]. The schedule for this transformation was dictated, in part, by receipt of an American Medical Association Grant, Accelerating Change in Medical Education [16] where OHSU's School of Medicine committed to rapidly transform to an entirely new curriculum in the first year of the grant, and graduating its first class in 2018.…”
Section: Methodsmentioning
confidence: 99%
“…Students review their performance data with coaches or advisors to identify areas of strength and further growth and goal setting. 9,11,12 Stakeholder feedback We found it important to have faculty member and assessment expertise in the development process. Our team comprised of software developers as well as experts in educational assessment and theory and faculty members from core content areas.…”
Section: Methods Of Assessment Visualisationmentioning
confidence: 99%
“…4,6 The data visualisation can provide efficient feedback, yet Hauer and colleagues found that students' use of this information to guide learning is variable: some students engaged in feedback to improve performance, whereas others did not. 4,9 Although clear communication of data via assessment dashboards is essential to provide feedback to various stakeholders, it should also mirror the CBME assessment schema.…”
Section: Assessment Reportingmentioning
confidence: 99%